1998
DOI: 10.1002/(sici)1097-4644(19980601)69:3<326::aid-jcb10>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Copper stimulates proliferation of human endothelial cells under culture

Abstract: Copper ions stimulate proliferation of human umbilical artery and vein endothelial cells but not human dermal fibroblasts or arterial smooth muscle cells. Incubation of human umbilical vein endothelial cells for 48 h with 500 microM CuSO4 in a serum-free medium in the absence of exogenous growth factors results in a twofold increase in cell number, similar to the cell number increase induced by 20 ng/ml of basic fibroblast growth factor under the same conditions. Copper-induced proliferation of endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
248
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(258 citation statements)
references
References 32 publications
(44 reference statements)
7
248
2
1
Order By: Relevance
“…Prior studies also showed that much lower doses (0.5 mM) of Cu 2þ ions do not influence SMC proliferation, although endothelial cells proliferated rapidly. 48 Here, we show that CuSO 4 in the range of 0.01 M induces SMC proliferation, results that suggest that the effect of Cu 2þ ions on cells is specific to cell type and dose. At the higher doses of CuSO 4 (0.1 M), although no cell death was observed, cells appeared rounded in the first 3 days after CuSO 4 addition but gradually assumed a more spread morphology.…”
Section: Discussionmentioning
confidence: 53%
“…Prior studies also showed that much lower doses (0.5 mM) of Cu 2þ ions do not influence SMC proliferation, although endothelial cells proliferated rapidly. 48 Here, we show that CuSO 4 in the range of 0.01 M induces SMC proliferation, results that suggest that the effect of Cu 2þ ions on cells is specific to cell type and dose. At the higher doses of CuSO 4 (0.1 M), although no cell death was observed, cells appeared rounded in the first 3 days after CuSO 4 addition but gradually assumed a more spread morphology.…”
Section: Discussionmentioning
confidence: 53%
“…Iron and copper are required by proliferating cancer cells during carcinogenesis [32,39,59,77] and high levels of iron and copper were found in certain tumour cells and tissues, including breast cancer cells [17,33]. As iron and copper metabolism is up-regulated in neoplastic tumours [29,39,41,44,47,59,62,65,72], 56MESS and other complexes in this class should be assessed, in combination with cisplatin, in the cancer models that have elevated iron and copper metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This is the level of DRI for Cu (0.9 mg/day) plus Cu supplementation (2 mg/day) for humans. It should note that many studies in cultured cells use high levels of Cu, ranging from 100 to 500 μM CuCl 2 or CuSO 4 [19][20][21].…”
Section: Discussionmentioning
confidence: 99%